Relationships Between the Changed Apparent Density of Recycled Handsheets and Their Mechanical and Physical Properties - Somwang Khantayanuwong; Supharp Keawmanee; Alisa Chusri (Agriculture and Natural Resources, 2006)
Relationships between the changed apparent density of recycled handsheets and their mechanical and physical properties were demonstrated. Recycled handsheets with decreased apparent density possessed decreased mechanical properties such as folding endurance, modulus of elasticity, and tensile strength. Changes in the brightness and opacity of recycled handsheets were consistent with the effect of the changed apparent density of paper on its brightness and opacity due to beating and wet pressing. This was possibly because the decreased apparent density meant there were lots of air voids in the handsheet structure due to the loss in conformability and flexibility of less-swollen-recycled fibers as well as the lost mass of handsheets during recycling. The loss in swelling capability of wet fibers with recycling could be determined by light microscopy and the WRVs of the fibers. In this study, it seemed that handsheets produced from softwood bleached kraft pulp fibers could considerably retain some of their mechanical properties and opacity with good brightness when recycling not more than twice without additional chemical and mechanical treatments.